9n-35=3n-9

Simple and best practice solution for 9n-35=3n-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9n-35=3n-9 equation:


Simplifying
9n + -35 = 3n + -9

Reorder the terms:
-35 + 9n = 3n + -9

Reorder the terms:
-35 + 9n = -9 + 3n

Solving
-35 + 9n = -9 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
-35 + 9n + -3n = -9 + 3n + -3n

Combine like terms: 9n + -3n = 6n
-35 + 6n = -9 + 3n + -3n

Combine like terms: 3n + -3n = 0
-35 + 6n = -9 + 0
-35 + 6n = -9

Add '35' to each side of the equation.
-35 + 35 + 6n = -9 + 35

Combine like terms: -35 + 35 = 0
0 + 6n = -9 + 35
6n = -9 + 35

Combine like terms: -9 + 35 = 26
6n = 26

Divide each side by '6'.
n = 4.333333333

Simplifying
n = 4.333333333

See similar equations:

| (6m-7)(2m+12)=0 | | 3x+52-21=14 | | 7+65x=39x+19 | | 0.5Q-p=0 | | x+(x+1)+(x+2)=2(x+2)+1 | | (3h-7)(5h+4)=0 | | 3x+3=45x-81 | | (4k-2)(3k+6)=0 | | 0.2x+5.4=2x | | (m+11)(m-9)=0 | | 7(k-3)=k-5 | | (k+4)(3k-12)=0 | | (2x-1)*(5x+72)=250 | | (p-5)(p+2)=0 | | (p-5)(p+2)=0 | | 16t^2-49=0 | | b^2+7b+4=0 | | 5m+2=24 | | 4k=9 | | 3x+59-21=14 | | 318=10x | | 2x+y=xy | | (4y-8)(3y+7)=0 | | 100x+100=200 | | 100x-100x=212 | | 8x^3-12x^2-18x+17=0 | | 5+6x=56 | | 0.5ln+ln= | | 0.06x+0.08*(18000-x)=1290 | | 4x^4-13x^2-75=0 | | 0.5ln= | | X+97=10x-20 |

Equations solver categories